2014
DOI: 10.3389/fnhum.2014.00982
|View full text |Cite
|
Sign up to set email alerts
|

Action verbs are processed differently in metaphorical and literal sentences depending on the semantic match of visual primes

Abstract: Language comprehension requires rapid and flexible access to information stored in long-term memory, likely influenced by activation of rich world knowledge and by brain systems that support the processing of sensorimotor content. We hypothesized that while literal language about biological motion might rely on neurocognitive representations of biological motion specific to the details of the actions described, metaphors rely on more generic representations of motion. In a priming and self-paced reading paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 88 publications
(127 reference statements)
3
9
0
Order By: Relevance
“…Our current findings are further in accordance with results of other studies proposing a gradual involvement of motor representations in abstract action language processing (Desai et al, 2011(Desai et al, , 2013Romero Lauro et al, 2013;Sakreida et al, 2013;Troyer, Curley, Miller, Saygin, & Bergen, 2014). Desai et al (2011) compared brain activation patterns in response to arm/hand related action verbs, which were embedded in literal and metaphoric contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Our current findings are further in accordance with results of other studies proposing a gradual involvement of motor representations in abstract action language processing (Desai et al, 2011(Desai et al, , 2013Romero Lauro et al, 2013;Sakreida et al, 2013;Troyer, Curley, Miller, Saygin, & Bergen, 2014). Desai et al (2011) compared brain activation patterns in response to arm/hand related action verbs, which were embedded in literal and metaphoric contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the results demonstrated that this effect is precluded when an action verb is presented in a painful semantic context. Altogether, these findings accord with previous results that have shown that semantic context affects the relationship between action words and the motor system (Aravena et al, 2014;Aravena et al, 2012;Bidet-Ildei et al, In press;Gilead et al, 2013;Taylor & Zwaan, 2008;Troyer et al, 2014;van Dam et al, 2014;van Dam et al, 2012;Zwaan et al, 2010). Moreover, they demonstrate that pain suggested in the sentences directly precludes the relationship between action verbs and BM detection.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, when processing point-light BM, observers are able to access an actor's characteristics, such as gender (Kozlowski & Cutting, 1977;Troje, Sadr, Geyer, & Nakayama, 2006), identity (Beardsworth & Buckner, 1981;Loula, Prasad, Harber, & Shiffrar, 2005), emotions (Atkinson, Dittrich, Gemmell, & Young, 2004;Chouchourelou, Matsuka, Harber, & Shiffrar, 2006) and intentions (Iacoboni et al, 2005;Martel, Bidet-Ildei, & Coello, 2011). In relation to embodied cognition theory, which postulates that language, abstract and symbol processing emerge from sensorimotor experience (Barsalou, 1999;Wilson, 2002), some studies have shown that BM perception is also related to higher-level cognitive processes, such as action-word processing (Bidet-Ildei, Sparrow, & Coello, 2011;Bidet-Ildei & Toussaint, 2015;Springer, Huttenlocher, & Prinz, 2012;Springer & Prinz, 2010;Troyer, Curley, Miller, Saygin, & Bergen, 2014). For example, Bidet-Ildei et al (2011) show that reading an action verb facilitates the subsequent detection of congruent point-light action embedded in a high-density dynamical point light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that detailed motor representations are linked to concrete action language processing, whereas abstract action language processing might be linked to rather broad motor representations. Troyer, Curley, Miller, Saygin, and Bergen () came to a similar conclusion. They used point light walkers as visual action primes and had participants read literal and metaphoric action sentences.…”
Section: Discussionmentioning
confidence: 63%